The Learning Academic in Social Studies Research and Culture Grade 3 Primary School Level Using the Website, Set of “Wan Somkun Tang Paputtasansana” - Nuenoi, Konchanok (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this research were 1. to develop and determine the efficiency of a learning website entitled “Buddhist Holy Days” for Grade 3 students, with the efficiency criterion set at 80/80, and 2. to compare the learning achievement in Social Studies, Religion, and Culture on the topic of Buddhist Holy Days before and after instruction through the website. The sample group consisted of 25 Grade 3 students from one classroom at Tessaban 1 Talad Kao School, Krabi Province, during the second semester of the 2024 academic year. The sample was selected using purposive sampling. The research instruments were: 1. the learning website on Buddhist Holy Days, 2. lesson plans using the website, and 3. an achievement test with a reliability coefficient of 0.90. Data were analyzed using percentage, mean, standard deviation, and the dependent samples t-test. The results revealed that: 1. the learning website on Buddhist Holy Days in the subject of Social Studies, Religion, and Culture for Grade 3 students was efficient according to the 80/80 criterion; and 2. students’ post-test learning achievement scores were significantly higher than their pre-test scores at the .05 level of statistical significance. This indicates that learning management through the “Buddhist Holy Days” website in Social Studies, Religion, and Culture for Grade 3 students effectively enhanced their knowledge and understanding.